2019
DOI: 10.4103/ijcm.ijcm_39_19
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment of tribal women in Kainatty, Wayanad: A cross-sectional study

Abstract: Introduction:Women from a society reflect the culture that they are a part of and tribal women are the most disadvantaged considering the levels of illiteracy and ignorance. As per the National Family Health Survey 4 reports, in Kerala, undernutrition is particularly common among women from scheduled tribes, 20%. This study was done to assess the nutritional status and its associated factors among tribal women in the reproductive age group at Wayanad.Materials and Methods:A hospital-based cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Based on BMI scores, a higher prevalence of malnutrition co-existing with poor oral health was reported amongst Nepal the primary school children consuming SLT in Pakistan (30) . Similarly, a higher prevalence of undernutrition was found among those tribal women who were SLT users in Wayanad, India (31) . Low consumption of fruits and vegetables (90 % below recommended levels) has been found among the SLT users in Bangladesh (32) .…”
Section: Smokeless Tobacco and Malnutritionmentioning
confidence: 83%
“…Based on BMI scores, a higher prevalence of malnutrition co-existing with poor oral health was reported amongst Nepal the primary school children consuming SLT in Pakistan (30) . Similarly, a higher prevalence of undernutrition was found among those tribal women who were SLT users in Wayanad, India (31) . Low consumption of fruits and vegetables (90 % below recommended levels) has been found among the SLT users in Bangladesh (32) .…”
Section: Smokeless Tobacco and Malnutritionmentioning
confidence: 83%
“…In contrast, a positive association was not elicited with the educational levels of tribal women in Kainatty and their nutritional status. 16,17 But the prevalence of undernutrition might be due to the use of smoking tobacco among them. 18 Probably due to similar reasons we have found undernutrition (33.33%) among Sabar adult males in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Sreelekshmi et al also revealed similar results in a study conducted among tribal women at Palakkad district, Kerala. 25…”
Section: Discussionmentioning
confidence: 99%